Abbildende Ellipsometrie mit Lichtwegumkehrung für die optische Charakterisierung von gekrümmten Oberflächen - Negara, Christian Emanuel (Schriftenreihe Automatische Sichtprüfung und Bildverarbeitung, 2023)
Ellipsometry is a measuring method for surface characterization and thin-film measurement of flat surfaces using polarized light. However, a new measuring principle based on return-path ellipsometry and retroreflection enables the detection of free-form surfaces. This new measurement principle and related questions regarding the measurement function, evaluation algorithms and ambiguities as well as degrees of freedom of the solution set are examined in this work.